2020
DOI: 10.1093/biolre/ioaa064
|View full text |Cite
|
Sign up to set email alerts
|

Testis-specific serine kinase protein family in male fertility and as targets for non-hormonal male contraception†

Abstract: Male contraception is a very active area of research. Several hormonal agents have entered clinical trials, while potential non-hormonal targets have been brought to light more recently and are at earlier stages of development. The general strategy is to target genes along the molecular pathways of sperm production, maturation, or function, and it is predicted that these novel approaches will hopefully lead to more selective male contraceptive compounds with a decreased side effect burden. Protein kinases are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 79 publications
1
34
0
Order By: Relevance
“…According to our results, Tssk1/2 distributes in spermatids and spermatozoa of A. irradians, which is in accordance with our assumption of its expression in the late-phase male germ cells based on the qRT-PCR assay. This expression pattern is also similar with that of Tssk1 and Tssk2 in vertebrates (Li et al, 2011;Salicioni et al, 2020), suggesting that the role of Tssk1/2 in spermatogenesis could be conserved in bilaterian animals. Tssk5 of A. irradians possesses the S_TKc domain, in which a conserved serine/threonine protein kinases active site was found.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…According to our results, Tssk1/2 distributes in spermatids and spermatozoa of A. irradians, which is in accordance with our assumption of its expression in the late-phase male germ cells based on the qRT-PCR assay. This expression pattern is also similar with that of Tssk1 and Tssk2 in vertebrates (Li et al, 2011;Salicioni et al, 2020), suggesting that the role of Tssk1/2 in spermatogenesis could be conserved in bilaterian animals. Tssk5 of A. irradians possesses the S_TKc domain, in which a conserved serine/threonine protein kinases active site was found.…”
Section: Discussionsupporting
confidence: 75%
“…According to the qRT-PCR assay and in situ hybridization results, all the five Tssk transcripts displayed the same expression pattern in the scallop testis. The accumulation of Tssks in spermatids or spermatozoa is similar to vertebrates ( Li et al, 2011 ; Salicioni et al, 2020 ), suggesting that the involvement of Tssks in testis development could be conserved across taxa. However, it raises questions such as why it’s necessary to have five Tssks in the scallop and what’s the functional difference between these genes.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Studies have confirmed that TSSK family is expressed after meiosis in male germ cells and mature mammalian sperm. When TSSK family expression is restricted after meiosis, it can affect sperm development through phosphorylation signal transduction ( Wang et al, 2015 , 2016 ; Salicioni et al, 2020 ). Animal experiments have confirmed ( Spiridonov et al, 2005 ) that male mice knocked out of the TSSK6 gene can cause spermatogenesis disorders, including decreased sperm count, decreased motility and survival rate, and increased number of abnormal sperm.…”
Section: Discussionmentioning
confidence: 99%
“…The testis-specific serine/threonine-protein kinase 3 (TSSK3), centrin 2 (CETN2), cation channel sperm associated 3 (CATSPER3) and sperm surface protein 17 (SPA17) were upregulated specifically in gonad. TSSK3 is a protein involved in the development and maturation of male germ cell [54]. TSSK3 role as a key regulator in spermiogenesis of the Scallop Argopecten irradians has recently been described [55].…”
Section: Discussionmentioning
confidence: 99%